Present status of trichinellosis - a neglected zoonosis in India - RAM, HIRA; GARG, RAJAT; BANERJEE, P S; SINGH, RAJ KUMAR (The Indian Journal of Animal Sciences, 2018)
Trichinellosis is a meat-borne helminthic zoonosis, caused by different species of the genus Trichinella. The disease is cosmopolitan in distribution and affects around 10,000 people annually around the globe. Based on genetic, biochemical and biological variability, 9 valid species (T. britovi, T. murrelli, T. nativa, T. nelsoni, T. papuae, T. patagoniensis, T. pseudospiralis, T. spiralis and T. zimbabwensis) and 3 genotypes (Trichinella T6, T8 and T9) of the parasite have been recognized. These species infect around 100 mammalian species including domestic and wild pigs, horses, game animals and wild carnivores. The infection starts with consumption of raw or undercooked meat or meat products containing encysted muscle larvae of the parasite. Most of the infections or outbreaks have been associated with the consumption of meat or meat products of pigs, wild boars, horses, crocodiles, walruses and dogs. Trichinoscopy is used in the veterinary inspection of pork in slaughterhouses and meat-packing facilities in many countries. It is a rapid process, but low in sensitivity and fails to detect mild infection. The muscle digestion method using HCl-pepsin is more sensitive and thus preferred. Recent outbreak of trichinellosis in Uttarakhand state opened up issues related to rapid diagnosis and lack of consumer awareness regarding safe cooking habits of meat of pig origin. This status report is an attempt to compile the information on Trichinella spp. infection in animals and humans in India at one place to draw the attention of medical and veterinary personnels involved in disease investigation and active research on zoonotic diseases.